The effect of water exercise on pain intensity and disability in pregnant women with low back pain: A clinical trial - Masoumeh Rezaei Niaraki; Hamideh Pakniat; Maryam Mafi; Fatemeh Ranjkesh (Mashhad University of Medical Sciences, 2021)
Introduction: Low back pain is one of the most common and costly problems during pregnancy. Exercise is one of the therapeutic strategies. Therefore, this study was performed with aim to determine the effect of water exercise on improving pain and disability in pregnant women with low back pain. Methods: This randomized clinical trial study was conducted on 54 pregnant women with low back pain referred to the healthcare centers in Qazvin in 2019. The subjects were randomly divided into two groups of intervention and control using block allocation. The intervention group participated in 24 sessions of water exercise from 20 to 34 weeks of pregnancy. The control group received the standard prenatal care. The Roland-Morris Questionnaire (RMQ) and the Visual Analogue Scale (VAS) were completed before, 4 and 8 weeks after the intervention in both groups. Data were analyzed by SPSS software (version 24) and U Mann-Whitney and Friedman tests. P< 0.05 was considered statistically significant. Results: Water exercise had significant effect on the mean score of pain intensity (1.44±1.42, 8.14±1.76) and the disability of low back pain (3.44±2.45, 17.29±2.98) in the intervention group compared to the control group after 8 weeks of intervention (p<0.001). Conclusion: Water exercise during pregnancy can improve pain intensity and disability in women with low back pain; it is recommended as a non-pharmacological method for low-risk pregnant women with low back pain.